Quantitative Risk Assessment for Equipments in Gas Processing Unit at The Topside of Offshore Platform - HADYANSYAH (NIM13103104), REZA
Risk is presented as the product of the outcomes of an event to happen (consequence of failure) and the probability of that event to happen (probability of failure). In process and oil & gas industries, the failure event is a factor of degradation mechanism and it meant to be the failure of pressure boundaries such as pipe wall, pressure vessel wall, etc. The activity in assessing the level of existing risks is called "risk assessment", which has to be carried in accordance to relevant codes concerning to it. In this final project, software has been developed to calculate risk assessment analysis for equipment including calculation for CoF and PoF based on DNV-RP-G101. The case study is conducted to the equipment for gas processing unit, located in Hang Tuah platform in Natuna Sea. From the result using the risk assessment, risk level for safety consequence risk and economic consequence risk, the highest risk category for equipment is medium high. Equipment that has category medium high safety consequence risk is 2nd stage suction scrubber and equipment that has category medium high economic consequence risk is 1st stage suction scrubber.